Strategi Penanganan Risiko Bencana Abrasi di Kawasan Pesisir Pantai Holtekamp Kota Jayapura - Heri Purnomo; Janviter Manalu; Johnson Siallagan; Auldry F. Walukow; Maklon Warpur (Pusat riset dan Inovasi Nasional, 2025)
Holtekamp Beach is a coastal area in Jayapura City that is very prone to abrasion due to sea waves because it is located directly opposite the Pacific Ocean. Abrasion and environmental damage on the coast of Holtekamp Beach are influenced by several interconnected factors that can have an impact on environmental problems. The research aims to analyze the impact of abrasion on the Holtekamp coastal area using survey and interview methods. Furthermore, data analysis is carried out by utilizing SWOT Analysis. This research was conducted from May to June 2025. The results showed that there are 4 (four) priority strategies that can be used as a basis for developing a strategy for Abrasion Disaster Risk Management Strategy in the Holtekamp Coastal Area of Jayapura City, namely; a) Increasing cooperation & coordination between stakeholders, namely the community and local government in achieving abrasion disaster management programs in the Holtekamp Coastal Area of Jayapura City; b) Optimizing supervision of development development/tourist lodges in the coastal area of Holtekamp Beach; c) Community participation is needed to maintain infrastructure that has been built and increase their awareness of environmental issues.d) Construction of wave breakers that function to reduce waves.